2009
DOI: 10.1186/1476-0711-8-18
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of tigecycline in combination with various antimicrobials against multidrug resistant Acinetobacter baumannii

Abstract: Background: Infections sustained by multidrug-resistant (MDR) and pan-resistant Acinetobacter baumannii have become a challenging problem in Intensive Care Units. Tigecycline provided new hope for the treatment of MDR A. baumannii infections, but isolates showing reduced susceptibility have emerged in many countries, further limiting the therapeutic options. Empirical combination therapy has become a common practice to treat patients infected with MDR A. baumannii, in spite of the limited microbiological and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 52 publications
6
81
2
3
Order By: Relevance
“…In a study conducted in 2012, it was emphasized that the use of inappropriate antibiotic combination increases CL resistance. 27 Principe et al 7 for the first time reported that they have noticed the synergy between TGC and CL by TK method in one A. baumannii isolate. In two studies conducted by CB method in TGC-CL combination 28 and in TGC-sulbactam, TGC-CL combinations 29 a synergistic effect was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study conducted in 2012, it was emphasized that the use of inappropriate antibiotic combination increases CL resistance. 27 Principe et al 7 for the first time reported that they have noticed the synergy between TGC and CL by TK method in one A. baumannii isolate. In two studies conducted by CB method in TGC-CL combination 28 and in TGC-sulbactam, TGC-CL combinations 29 a synergistic effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, combined use of antibiotics is recommended to prevent the development of resistance and increase the success in the treatment of MDR A. baumannii infections since. 7,19,20 Recent studies in Turkey found that imipenem-netilmicin, In this study, the interactions of TGC and CL combinations with different antibiotics; AK, CIP, MR, MXF, RF and each other were investigated by CB and TK methods. The best synergistic effect was detected in the CL combinations by CB method, for CL-RF (100%), CL-MR (100%), and in the TGC combinations for TGC-RF (53%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Although these studies show better microbiological response with combination therapy, clinical cure and mortality remains unaffected.…”
Section: Introductionmentioning
confidence: 99%